MENINGKATKAN KEMAMPUAN BERPIKIR ALJABAR SISWA DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Musyrifah, Eva; Nurasiah, Desy; Hafiz, M. (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractAlgebraic thinking ability is the ability needed to analyze, generalize, model, prove, predict, and solve problems using symbols, patterns, and numbers presented in the form of words, diagrams, tables, graphs, and equations. Students' algebraic thinking skills still need to improve. This study aimed to test and determine the effect of the RME approach on students' algebraic thinking skills. This research is a type of quasi-experimental research with a research design using a Randomized Posttest Only Control Group Design. The research subjects were X IPA group students, as many as 60 people. The sample determination was carried out using the Cluster Random Sampling technique. Data collection techniques using student algebraic thinking ability tests in the form of descriptions totaling 8 items, documentation studies, and interviews. The results showed an effect of the RME approach on students' algebraic thinking skills, and the effect was classified as moderate. Therefore, RME can be an alternative learning model that can be used to improve students' algebraic thinking skills.AbstrakKemampuan berpikir aljabar adalah kemampuan yang dibutuhkan untuk menganalisis, menggeneralisasi, memodelkan, membuktikan, memprediksi, dan memecahkan masalah, dengan menggunakan simbol, pola dan bilangan yang disajikan dalam bentuk kata, diagram, tabel, grafik, dan persamaan. Kemampuan berpikir aljabar siswa masih rendah. Tujuan dari penelitian iniadalah menguji dan mengetahui besarnya pengaruh pendekatan RME terhadap kemampuan berpikir aljabar siswa. Penelitian ini merupakan jenis penelitian kuasi eksperimen dengan rancangan penelitian menggunakan Randomized Posttest Only Control Group Design. Subjek penelitian adalah siswa kelompok X IPA sebanyak 60 orang. Penentuan sampel dilakukan dengan teknik Cluster Random Sampling. Teknik pengumpulan data menggunakan tes kemampuan berpikir aljabar siswa berbentuk uraian berjumlah 8butir soal, studi dokumentasi, dan wawancara. Analisis data menggunakan uji t. Hasil penelitian menunjukkan bahwa terdapatpengaruh pendekatan RME terhadap kemampuan berpikir aljabar siswa dan pengaruhnya tergolong kategori sedang. Oleh karena itu RME dapat menjadi alternatif model pembelajaran yang dapat digunakan untuk meningkatkan kemampuan berpikir aljabar siswa.